Synthesis of different heterocyclic compounds derived from some amino acids (Journal of the College of Basic Education, 2022)
Some of heterocyclic compounds have been synthesized using some amino acids as a starting materials provides that the synthesized products bear parts of the amino acids structure. The types of these compounds are pyrazoles, pyridazines, thiazepines, and oxazepines. A preliminary test to evaluate the antimicrobial potency of some of the synthesized compounds were carried out using two types of organisms (+ve) and (-ve). The tests demonstrated an encouraging results for a good number of the tested compounds.